Distance measurement of a noncovalently bound Y@C82 pair with double electron electron resonance spectroscopy - Gil-Ramirez, G; Shah, A; El Mkami, H; Porfyrakis, K; Briggs, G; Morton, J; Anderson, H; Lovett, J (American Chemical Society, 2018)
Paramagnetic endohedral fullerenes with long spin coherence times, such as N@C60 and Y@C82, are being explored as potential spin quantum bits (qubits). Their use for quantum information processing requires a way to hold them in fixed spatial arrangements. Here we report the synthesis of a porphyrin-based two-site receptor 1, offering a rigid structure that binds spin-active fullerenes (Y@C82) at a center-to-center distance of 5.0 nm, predicted from molecular simulations. The spin–spin dipolar coupling was measured with the pulsed EPR spectroscopy technique of double electron electron resonance and analyzed to give a distance of 4.87 nm with a small distribution of distances.